Modified three-dimensional porous carbon-based silicon-carbon negative electrode material and preparation method thereof
By granulating and activating the fine powder produced during the porous carbon preparation process, and combining carbon coating technology, a modified three-dimensional porous carbon-based silicon carbon negative electrode material was prepared, which solved the problems of waste of fine powder and poor structural stability, and achieved efficient electrochemical performance improvement.
Patent Information
- Application Number
- CN202411906815.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-03-28
AI Technical Summary
There are existing problems such as waste of fine powder generated during the preparation of porous carbon, poor stability of porous matrix pore structure, and serious collapse of the lattice structure of the material during the repeated embedding of lithium ions.
By mixing the fine powder with the binder, sintering and granulating under an inert atmosphere, forming larger particles, and then activation and carbon coating, a modified three-dimensional porous carbon-based silicon carbon negative electrode material was prepared.
The waste reuse is achieved, the material conductivity and structural stability are improved, the volume expansion of the silicon-based negative electrode is alleviated, and the specific capacity and circulation performance are improved.
Smart Images

Figure CN119706838A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of silicon-carbon negative electrode materials, and in particular to a modified three-dimensional porous carbon-based silicon-carbon negative electrode material and a preparation method thereof. Background Art
[0002] At present, a large number of commercial lithium-ion batteries mainly use graphite as the negative electrode material (the maximum specific capacity does not exceed 372mAh / g), which is difficult to meet the needs of scientific and technological development. The maximum theoretical specific capacity of silicon is as high as 4200mAh / g, which provides great room for improvement for high-capacity and high-density lithium-ion batteries. However, silicon has a volume expansion of up to 300% during the alloying / de-alloying process, which can easily cause problems such as electrode sheet rupture, active material shedding, and rapid battery performance degradation. In addition, the cracking and pulverization of silicon will cause the new silicon layer to be exposed, resulting in the continuous generation of the solid electrolyte interface (SEI) film, which consumes the active lithium inside the battery, thereby limiting the practical application of silicon as the negative electrode of lithium-ion batteries.
[0003] To address the problem of volume expansion of silicon negative electrodes, the main improvement methods include nano-sizing silicon particles or compounding them. However, nano-sized silicon has the disadvantages of easy agglomeration, high preparation cost, and complex process, which makes it difficult to use in practice. Compounding silicon with other materials has more selectivity and flexibility. Carbon encapsulation can inhibit the surface oxidation of silicon and stabilize the SEI layer. Adding porous conductive materials to the negative electrode is beneficial to improving the lithium ion transmission capacity and the release of volume expansion stress, thereby obtaining a highly stable negative electrode. Summary of the invention
[0004] The purpose of the present invention is to provide a modified three-dimensional porous carbon-based silicon-carbon negative electrode material and a preparation method thereof, which is used to solve the problems of waste of fine powder generated in the existing preparation process of porous carbon, poor stability of the pore structure of the porous matrix, and serious collapse of the material lattice structure caused by repeated insertion and extraction of lithium ions.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] The present invention provides a method for preparing a modified three-dimensional porous carbon-based silicon-carbon negative electrode material, comprising the following steps:
[0007] S1, carbonizing the carbon source 1 at high temperature under an inert atmosphere, and cooling it to room temperature to obtain a carbon precursor Q1;
[0008] S2, activating and sintering the carbon precursor Q1 under an inert atmosphere, and cooling to room temperature to obtain a porous carbon precursor Q2;
[0009] S3, crushing and sieving the porous carbon precursor Q2 to obtain porous carbon and fine powder Q3;
[0010] S4, mixing the fine powder Q3 with a binder, sintering and granulating under an inert atmosphere to obtain a carbon precursor Q4;
[0011] S5, activating and sintering the carbon precursor Q4 under an inert atmosphere to obtain a porous carbon precursor Q5;
[0012] S6, depositing silane gas on the porous carbon precursor Q5 under an inert atmosphere to obtain a modified three-dimensional porous carbon / silicon precursor Q6;
[0013] S7. Under inert atmosphere conditions, introduce carbon source 2 into the modified three-dimensional porous carbon / silicon precursor Q6 for carbon coating to obtain a modified three-dimensional porous carbon-based silicon / carbon negative electrode material.
[0014] Further, the carbon source 1 comprises a biomass carbon source and a resin carbon source, the biomass carbon source comprises one or more of sugar cane, bark, wood, straw and coconut shell; the resin carbon source comprises epoxy resin and / or phenolic resin;
[0015] In the step S1, the temperature of high temperature carbonization is 400-800° C., and the time of high temperature carbonization is 1-3 hours.
[0016] Furthermore, the inert atmosphere independently contains a mixture of one or more of argon, helium and nitrogen.
[0017] Furthermore, in step S2, the activation includes physical activation or alkali activation, wherein the physical activation is to introduce CO 2 or water vapor, with a flow rate of 0.5 to 5 L / min; the alkaline activation is performed by using an alkaline reagent, the alkaline reagent comprises potassium hydroxide and / or sodium hydroxide, and the mass ratio of the carbon precursor Q1 to the alkaline reagent is 1:2 to 10;
[0018] The sintering temperature is 500-900° C., and the sintering time is 2-6 hours.
[0019] Furthermore, in step S3, the crushing includes one or more of grinding, mechanical crushing and air flow crushing.
[0020] Furthermore, in step S4, the binder comprises asphalt; the mass ratio of the fine powder Q3 to the binder is 10 to 30:1;
[0021] The sintering temperature is 200-600° C., and the sintering time is 2-6 hours.
[0022] Furthermore, in step S5, the activation includes physical activation or alkali activation, wherein the physical activation is to introduce CO 2or water vapor, with a flow rate of 0.5 to 5 L / min; the alkaline activation is performed by using an alkaline reagent, the alkaline reagent comprises potassium hydroxide and / or sodium hydroxide, and the mass ratio of the carbon precursor Q4 to the alkaline reagent is 1:2 to 10;
[0023] The sintering temperature is 500-900° C., and the sintering time is 2-6 hours.
[0024] Furthermore, in step S6, the silane gas is one or more of silane, disilane, tetrafluorosilane, hexamethyldisilane, dichlorodimethylsilane and trimethylsilane, and the flow rate of the silane gas is 0.5 to 8 L / min; the flow ratio of the silane gas to the inert atmosphere is 1:1 to 15, the deposition temperature is 400 to 1000°C, the deposition time is 60 to 480 min, and the heating rate is 4 to 10°C / min.
[0025] Furthermore, in step S7, the carbon source 2 comprises one or more of methane, ethane, propane, acetylene, propyne, acetone and cyclohexane, and the flow rate of the carbon source 2 is 0.5 to 8 L / min; the flow ratio of the carbon source 2 to the inert atmosphere is 1:1 to 15; the temperature of the carbon coating is 600 to 900°C, the carbon coating time is 60 to 480 min, and the heating rate is 4 to 10°C / min.
[0026] The invention provides a modified three-dimensional porous carbon-based silicon-carbon negative electrode material, wherein the content of Si in the modified three-dimensional porous carbon-based silicon-carbon negative electrode material is 10-90%, and the content of C is 10-90%.
[0027] Beneficial effects of the present invention:
[0028] (1) The fine powder produced during the crushing process of porous carbon cannot be reused. The fine powder is bonded together by granulation to form larger particles, which are then activated to form porous carbon, thus achieving waste recycling.
[0029] (2) The particles formed by granulation have a smaller particle size, which can shorten the lithium ion diffusion path and increase the ion diffusion rate, thereby improving the battery's rate performance.
[0030] (3) Smaller particles can reduce the volume expansion of the material during the charging and discharging process, improve the stability of the silicon-carbon negative electrode material structure, and thus improve the coulombic efficiency and cycle performance of the material.
[0031] (4) The porous carbon formed by granulation and activation has a three-dimensional conductive network structure, which can improve the electronic conductivity and thus improve the rate performance of the silicon-carbon negative electrode. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1The present invention is a process flow chart for preparing modified three-dimensional porous carbon-based silicon-carbon negative electrode materials. DETAILED DESCRIPTION
[0033] The present invention provides a method for preparing a modified three-dimensional porous carbon-based silicon-carbon negative electrode material, comprising the following steps:
[0034] S1, carbonizing the carbon source 1 at high temperature under an inert atmosphere, and cooling it to room temperature to obtain a carbon precursor Q1;
[0035] S2, activating and sintering the carbon precursor Q1 under an inert atmosphere, and cooling to room temperature to obtain a porous carbon precursor Q2;
[0036] S3, crushing and sieving the porous carbon precursor Q2 to obtain porous carbon and fine powder Q3;
[0037] S4, mixing the fine powder Q3 with a binder, sintering and granulating under an inert atmosphere to obtain a carbon precursor Q4;
[0038] S5, activating and sintering the carbon precursor Q4 under an inert atmosphere to obtain a porous carbon precursor Q5;
[0039] S6, depositing silane gas on the porous carbon precursor Q5 under an inert atmosphere to obtain a modified three-dimensional porous carbon / silicon precursor Q6;
[0040] S7. Under inert atmosphere conditions, introduce carbon source 2 into the modified three-dimensional porous carbon / silicon precursor Q6 for carbon coating to obtain a modified three-dimensional porous carbon-based silicon / carbon negative electrode material.
[0041] In the present invention, the carbon source 1 comprises a biomass carbon source and a resin carbon source, wherein the biomass carbon source is preferably one or more of sugar cane, bark, wood, straw and coconut shell; and the resin carbon source is preferably epoxy resin and / or phenolic resin.
[0042] In the present invention, in step S1, the temperature of high temperature carbonization is 400-800°C, preferably 500-700°C, and more preferably 550-650°C; the time of high temperature carbonization is 1-3h, and preferably 2h.
[0043] In the present invention, the inert atmosphere independently comprises a mixed gas of one or more of argon, helium and nitrogen, preferably nitrogen.
[0044] In the present invention, in step S2, the activation includes physical activation or alkali activation. The physical activation is to introduce CO 2or water vapor, with a flow rate of 0.5 to 5 L / min, preferably 1 to 4 L / min, and more preferably 2 to 3 L / min; the alkali activation is performed using an alkali reagent, and the alkali reagent is preferably potassium hydroxide and / or sodium hydroxide, and the mass ratio of the carbon precursor Q1 to the alkali reagent is 1:2 to 10, preferably 1:3 to 9, more preferably 1:4 to 8, and more preferably 1:5 to 6.
[0045] In the present invention, in the step S2, the sintering temperature is 500-900°C, preferably 600-800°C, and more preferably 700°C; the sintering time is 2-6h, preferably 3-5h, and more preferably 4h.
[0046] In the present invention, in step S3, the crushing is preferably one or more of grinding, mechanical crushing and air flow crushing.
[0047] In the present invention, in step S4, the binder is preferably asphalt; the mass ratio of the fine powder Q3 to the binder is 10 to 30:1, preferably 15 to 20:1.
[0048] In the present invention, in the step S4, the sintering temperature is 200-600°C, preferably 300-500°C, and more preferably 350-450°C; the sintering time is 2-6h, preferably 3-5h, and more preferably 4h.
[0049] In the present invention, in step S5, the activation includes physical activation or alkali activation. The physical activation is to introduce CO 2 or water vapor, with a flow rate of 0.5 to 5 L / min, preferably 1 to 4 L / min, and more preferably 2 to 3 L / min; the alkali activation is performed using an alkali reagent, the alkali reagent comprises potassium hydroxide and / or sodium hydroxide, and the mass ratio of the carbon precursor Q4 to the alkali reagent is 1:2 to 10, preferably 1:3 to 9, more preferably 1:4 to 8, and more preferably 1:5 to 6.
[0050] In the present invention, in the step S5, the sintering temperature is 500-900°C, preferably 600-800°C, and more preferably 700°C; the sintering time is 2-6h, preferably 3-5h, and more preferably 4h.
[0051] In the present invention, in step S6, the silane gas is preferably one or more of silane, disilane, tetrafluorosilane, hexamethyldisilane, dichlorodimethylsilane and trimethylsilane, and the flow rate of the silane gas is 0.5-8 L / min, preferably 1-7 L / min, more preferably 2-6 L / min, and more preferably 3-4 L / min; the flow ratio of the silane gas to the inert atmosphere is 1:1-15, preferably 1:2-12, and more preferably 1:5-10; the deposition temperature is 400-1000°C, preferably 500-900°C, and more preferably 600-800°C; the deposition time is 60-480 min, preferably 100-400 min; the heating rate is 4-10°C / min, preferably 5-9°C / min, and more preferably 6-8°C / min.
[0052] The present invention provides a modified three-dimensional porous carbon-based silicon-carbon negative electrode material, in which the Si content of the modified three-dimensional porous carbon-based silicon-carbon negative electrode material is 10-90%, preferably 20-80%, and more preferably 30-70%; the C content is 10-90%, preferably 20-80%, and more preferably 30-70%.
[0053] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0054] Example 1
[0055] S1, carbonizing coconut shell at 600°C for 2 h at a heating rate of 5°C / min under argon atmosphere, and then cooling to room temperature to obtain carbon precursor Q1;
[0056] S2, the carbon precursor Q1 obtained in S1 is heated in CO 2 (flow rate is 2 L / min), sintered at 600 °C for 2 h in an argon atmosphere, and cooled to room temperature to obtain a porous carbon precursor Q2;
[0057] S3, mechanically crushing and sieving the porous carbon precursor Q2 obtained in S2 to obtain porous carbon and fine powder Q3;
[0058] S4, the fine powder Q3 obtained in S3 is mixed with asphalt in a mass ratio of 15:1, and sintered at 450°C for 4h at a heating rate of 5°C / min in an argon atmosphere to obtain a carbon precursor Q4;
[0059] S5, the carbon precursor Q4 obtained in S4 is subjected to CO 2 (flow rate is 2 L / min) activation, sintering at 600 °C for 2 h, and cooling to room temperature to obtain porous carbon precursor Q5;
[0060] S6. In a nitrogen atmosphere, monosilane gas was deposited on the porous carbon precursor Q5 obtained in S5, and the temperature was raised to 550° C. at a heating rate of 4° C. / min, and the monosilane gas flow rate was 5 L / min (monosilane gas flow rate: N 2 flow rate = 1:2), deposition time 240 min; porous carbon-supported silicon precursor Q6 was obtained;
[0061] S7. Methane gas and nitrogen gas are introduced to achieve carbon coating on the porous carbon-loaded silicon precursor Q6. The ratio of methane gas flow rate to nitrogen flow rate is 1:5, the methane gas flow rate is 5L / min, the deposition temperature is 550℃, and the heating rate is 5℃ / min; the deposition time is 240min, and finally a modified three-dimensional porous carbon-based silicon-carbon negative electrode material is obtained, with a silicon content of 50% and a carbon content of 50%.
[0062] Example 2
[0063] The only difference from Example 1 is that the coconut shell in S1 is replaced by phenolic resin; the carbonization temperature is 600° C., the insulation time is 2 h, and the prepared modified three-dimensional porous carbon-based silicon-carbon negative electrode material has a Si content of 50% and a carbon content of 50%.
[0064] Example 3
[0065] The only difference from Example 1 is that in S6, the temperature is raised to 650°C at a heating rate of 4°C / min, and the monosilane gas flow rate is 5 L / min (monosilane gas flow rate: N 2 flow rate = 1:2), deposition time 240min, and the prepared modified three-dimensional porous carbon-based silicon-carbon negative electrode material had a Si content of 50% and a carbon content of 50%.
[0066] Example 4
[0067] The only difference from Example 2 is that in S6, the temperature is raised to 650°C at a heating rate of 4°C / min, and the monosilane gas flow rate is 2 L / min (monosilane gas flow rate: N 2 flow rate = 1:5), deposition time 300min, and the prepared modified three-dimensional porous carbon-based silicon-carbon negative electrode material has a Si content of 45% and a carbon content of 55%.
[0068] Example 5
[0069] The only difference from the first embodiment is that acetylene gas deposition is used in S7, and the flow rate of acetylene gas is 6 L / min (acetylene gas flow rate: N 2 flow rate = 1:5), the temperature of vapor deposition is 700°C, and the prepared modified three-dimensional porous carbon-based silicon-carbon negative electrode material has a Si content of 48% and a carbon content of 52%.
[0070] Comparative Example 1
[0071] The fine powder obtained from the epoxy resin is directly deposited without granulation, and monosilane is introduced under nitrogen protection, with the ratio of monosilane gas flow rate to nitrogen gas flow rate being 1:5, and the deposition temperature being 650°C; after the silane deposition is completed, acetylene gas is introduced under nitrogen protection, with the ratio of acetylene gas flow rate to nitrogen gas flow rate being 1:5; a silicon-carbon negative electrode material is prepared, with a Si content of 50% and a carbon content of 50%.
[0072] The modified three-dimensional porous carbon-based silicon-carbon negative electrode materials obtained in the above Examples 1 to 5 and the silicon-carbon negative electrode material obtained in Comparative Example 1 were subjected to performance tests, and the results are shown in Table 1 below.
[0073] Table 1 Test results of negative electrode materials in Examples 1 to 5 and Comparative Example 1
[0074]
[0075] From the above examples, it can be seen that the present invention provides a modified three-dimensional porous carbon-based silicon-carbon negative electrode material and a preparation method thereof. From the test results in Table 1 above, it can be seen that the first efficiency of the silicon-carbon negative electrode material prepared by the present invention can reach 92.7%, and the capacity retention rate can reach 87.9% after 50 cycles.
[0076] The present invention solves the problems of waste of fine powder generated in the existing process of preparing porous carbon, poor stability of the porous matrix pore structure, and serious collapse of the material lattice structure caused by repeated insertion and extraction of lithium ions. The fine powder generated in the process of preparing porous carbon is granulated to prepare porous carbon, and waste recycling is achieved. The prepared porous carbon has a three-dimensional conductive network structure, which can improve the conductivity of the material, alleviate the volume expansion of the silicon-based negative electrode, and improve the specific capacity and cycle performance of the silicon-based negative electrode material. The silicon-carbon negative electrode material prepared by the present invention has a three-dimensional conductive network structure, which improves the electronic conductivity and structural stability of the silicon-carbon negative electrode material, avoids structural collapse, and improves the specific capacity and cycle performance of the silicon-carbon negative electrode material.
[0077] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a modified three-dimensional porous carbon-based silicon-carbon negative electrode material, characterized in that: The following steps are involved: S1, carbonizing the carbon source 1 at high temperature under an inert atmosphere, and cooling it to room temperature to obtain a carbon precursor Q1; S2, activating and sintering the carbon precursor Q1 under an inert atmosphere, and cooling to room temperature to obtain a porous carbon precursor Q2; S3, crushing and sieving the porous carbon precursor Q2 to obtain porous carbon and fine powder Q3; S4, mixing the fine powder Q3 with a binder, sintering and granulating under an inert atmosphere to obtain a carbon precursor Q4; S5, activating and sintering the carbon precursor Q4 under an inert atmosphere to obtain a porous carbon precursor Q5; S6, depositing silane gas on the porous carbon precursor Q5 under an inert atmosphere to obtain a modified three-dimensional porous carbon / silicon precursor Q6; S7. Under inert atmosphere conditions, introduce carbon source 2 into the modified three-dimensional porous carbon / silicon precursor Q6 for carbon coating to obtain a modified three-dimensional porous carbon-based silicon / carbon negative electrode material.
2. The preparation method according to claim 1, characterized in that: The carbon source 1 comprises a biomass carbon source and a resin carbon source, wherein the biomass carbon source comprises one or more of sugar cane, bark, wood, straw and coconut shell; the resin carbon source comprises epoxy resin and / or phenolic resin; In the step S1, the temperature of high temperature carbonization is 400-800° C., and the time of high temperature carbonization is 1-3 hours.
3. The preparation method according to claim 2, characterized in that: The inert atmosphere independently comprises a mixed gas of one or more of argon, helium and nitrogen.
4. The preparation method according to any one of claims 1 to 3, characterized in that: In the step S2, the activation includes physical activation or alkaline activation, wherein the physical activation is to introduce CO2 or water vapor at a flow rate of 0.5 to 5 L / min; the alkaline activation is to use an alkaline reagent for activation, wherein the alkaline reagent includes potassium hydroxide and / or sodium hydroxide, and the mass ratio of the carbon precursor Q1 to the alkaline reagent is 1:2 to 10; The sintering temperature is 500-900° C., and the sintering time is 2-6 hours.
5. The preparation method according to claim 4, characterized in that: In the step S3, the crushing includes one or more of grinding, mechanical crushing and air flow crushing.
6. The preparation method according to claim 1, 2 or 5, characterized in that: In the step S4, the binder comprises asphalt; the mass ratio of the fine powder Q3 to the binder is 10 to 30:1; The sintering temperature is 200-600° C., and the sintering time is 2-6 hours.
7. The preparation method according to claim 6, characterized in that: In the step S5, the activation includes physical activation or alkaline activation, wherein the physical activation is to introduce CO2 or water vapor at a flow rate of 0.5 to 5 L / min; the alkaline activation is to use an alkaline reagent for activation, wherein the alkaline reagent includes potassium hydroxide and / or sodium hydroxide, and the mass ratio of the carbon precursor Q4 to the alkaline reagent is 1:2 to 10; The sintering temperature is 500-900° C., and the sintering time is 2-6 hours.
8. The preparation method according to claim 1 or 2 or 5 or 7, characterized in that: In step S6, the silane gas is one or more of silane, disilane, tetrafluorosilane, hexamethyldisilane, dichlorodimethylsilane and trimethylsilane, and the flow rate of the silane gas is 0.5 to 8 L / min; the flow ratio of the silane gas to the inert atmosphere is 1:1 to 15, the deposition temperature is 400 to 1000°C, the deposition time is 60 to 480 min, and the heating rate is 4 to 10°C / min.
9. The preparation method according to claim 8, characterized in that: In step S7, the carbon source 2 comprises one or more of methane, ethane, propane, acetylene, propyne, acetone and cyclohexane, and the flow rate of the carbon source 2 is 0.5 to 8 L / min; the flow ratio of the carbon source 2 to the inert atmosphere is 1:1 to 15; the temperature of the carbon coating is 600 to 900°C, the carbon coating time is 60 to 480 min, and the heating rate is 4 to 10°C / min.
10. The modified three-dimensional porous carbon-based silicon-carbon negative electrode material prepared by the preparation method according to any one of claims 1 to 9, characterized in that: The content of Si in the modified three-dimensional porous carbon-based silicon-carbon negative electrode material is 10-90%, and the content of C is 10-90%.
Citation Information
Cited By
Method for preparing porous carbon through secondary utilization of fine powder of porous carbon airflow powder
CN120589750A
A method for preparing porous carbon by secondary utilization of porous carbon gas flow fines
CN120589750B